Introduction: Social, cultural norms and women’s health - Gatison, A.M. (Communicating Women’s Health: Social and Cultural Norms that Influence Health Decisions, 2015)
In 2002, the Institute of Medicine published Unequal Treatment: Confronting Racial and Ethnic Disparities in Health Care, which reported that racial and ethnic minorities experience a lower quality of healthcare than nonminorities, even when they have income and insurance. That report pointed to stereotyping and bias within the healthcare system as the primary culprit and made recommendations about developing culturally competent healthcare as the fundamental way to reduce health disparities. Since then, cultural competency in health communication has become the touchstone for targeted health communication and disease prevention efforts for women and minorities. Unfortunately, this goal will never be achieved unless we hear from the women who continue to fall through the cracks of the still-broken healthcare system. Indeed, in the 21st century, there remain social and cultural norms that manifest themselves via institutional and interpersonal barriers to effective health communication along the lines of race, class, gender, ethnicity, and sexuality that unduly impact women as a group. These social and cultural norms are defined as a pattern of behavior in a particular group, community, or culture, accepted as normal and to which an individual is expected to conform. © 2016 Taylor & Francis.
Keywords: dept.com